PENGEMBANGAN MBKM MAHASISWA KKN UNIVERSITAS QUALITY TERHADAP PELAYANAN MASYARAKAT BIDANG PENDIDIKAN DI DESA SABUNGAN NIHUTA - Rakiyah, Siti; Sari, Nilam; Sitorus, Andreas Sihar Marudut (JURNAL CURERE, 2023)
The MBKM (The Freedom to Learn-Free Campus) policy is implemented in order to realize an autonomous and flexible learning process in higher education so that universities can design and implement innovative learning processes so that students can achieve learning outcomes covering aspects of attitude, knowledge and skills optimally. This policy also aims to increase links and matches with the business world and the industrial world, as well as to prepare students for the world of work from the beginning. One of the programs in the MBKM for students is to carry out KKN for students, in this activity each student works in the village for a certain period of time, lives and helps rural communities solve development problems as part of their curriculum, as was done by Quality University students in the village of Sabungan Nihuta Kec. Ronggur Nihuta Kab. Samosir. From this activity, research was carried out which aimed to develop the implementation of KKN activities for University of Quality students in the MBKM program in the village of Sabungan Nihuta Kec. Ronggur Nihuta Kab. Samosir uses a research method that is a descriptive method and will be published in the Curere journal at Quality University.